The Effects of Roasting Time of Unfermented Cocoa Liquor Using the Oil Bath Methods on Physicochemical Properties and Volatile Compound Profiles - Nurhayati Nurhayati; Francis Maria Constance Sigit Setyabudi; Djagal Wiseso Marseno; Supriyanto Supriyanto (agriTECH, 2019)
This study aimed to measure the effect of roasting time on physicochemical properties and volatile compounds of unfermented cocoa liquor roasted with an oil bath method. Physicochemical properties (pH, temperature, and color), flavor, and volatile compounds were analyzed. The results showed that the longer the roasting time the higher the unfermented cocoa liquor’s temperature, °Hue, and ΔE value, but lower pH and L value. There were 126 volatile compounds obtained by various roasting time, identified as pyrazines (12), aldehydes (16), esters (1), alcohols (31), acids (15), hydrocarbons (11), ketones (19), and others (21). At 15, 20, and 25 minutes of roasting time, 69, 74, and 67 volatile compounds, respectively, were identified. Volatile compounds’ profiles were indicated to be strongly influenced by roasting time. The largest area and highest number of compounds, such as pyrazines and aldehydes, were obtained at 20 minutes, which was also the only time the esters were identified. As well as the time showed a very strong flavor described by panelists.